Meningkatkan Transparansi dan Akuntabilitas Pemerintah Melalui Teknologi Digital dan Partisipasi Publik dalam Upaya Pemberantasan Korupsi - Wanda Aprilla; Mardalena Wulandari; Arie Elcaputera (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Corruption is one of the biggest challenges faced by many countries, including Indonesia. Corrupt practices not only harm the state’s finances but also erode public trust in the government. This study aims to explore how digital technology and public participation can be effectively used to enhance government transparency and accountability in efforts to combat corruption. This research employs a descriptive qualitative method with a literature review and document analysis approach. Data is collected from various relevant literature sources and official documents to analyze the use of digital technology and public participation in enhancing government transparency and accountability in anti-corruption efforts. The results show that digital technologies, such as e-government, e-procurement, blockchain, big data analytics, open data, whistleblowing systems, and digital payment systems, can facilitate broader and faster access to information and increase public participation in government oversight. Public participation, through active involvement in reporting and monitoring, can raise public awareness of corruption issues and strengthen anti-corruption efforts. This study concludes that the combination of digital technology and public participation has great potential to create a more transparent and accountable government. Recommendations include the development of better technological infrastructure, increased digital literacy among the public, and the promotion of public participation in oversight processes. By implementing these strategies, it is hoped that a cleaner and more trustworthy government can be achieved, ultimately improving public welfare.